Thomas Davenport correspondence - Davenport, Thomas, 1802-1851.; Cook, Ransom
Letters received chiefly by Davenport's business partner, Ransom Cook, relating to the company they formed, with workshops in Vermont and New York, to develop and promote the electromagnetic motor and to its application and use. Includes two letters from W.H.C. Bartlett requesting a machine for the use of his students at the United States Military Academy. Other correspondents include W.W. Ayres, Marcus Cook, and Nelson Cook, nephew and brothers of Ransom Cook, who were employees of the company.
Blacksmith, of Brandon, Vt., who constructed an electric motor in 1834 that was patented in 1837.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ayres, W. W. -- Correspondence; Bartlett, W. H. C. -- 1804-1893 -- Correspondence; Cook, Marcus -- Correspondence; Cook, Nelson -- Correspondence; Electric motors -- Design and construction -- New York (State); Electric motors -- Design and construction -- Vermont; Electromagnetism; United States Military Academy -- Students; Inventors